Design of a High Sea Wave Sensor System in Puger Beach - Ike Fibriani; Januar Fery Irawan; Alfredo Bayu Satriya; Satrio Budi Utomo; Widyono Hadi; Widjonarko Widjonarko; Khoiril Khoiril (University of Muhammadiyah Malang, 2020)
Indonesia is an archipelagic country that has a very wide sea area. Thus, Indonesian sea has a huge potential of natural resources that can be utilized to grow the nation's economy. There are many occupations and efforts that can be done to increase the income from the sea and also to conserve it. Fishery is one of the most effective way to gain the sea resources; however, fishery is limited by the weather condition on the sea. This is also a problem that happened in Puger Beach. Puger Beach is located in the south Jember and it faces the Hindia Ocean, which means the weather condition is more dangerous for fishermen than other part of coastal. To ensure the safety of the fishermen, the weather condition on the sea must be evaluated and predicted before the fishery. This study designed a system to provide fishermen in Puger Beach an information about sea and beach weather condition which consist of wave height prediction, wind speed, temperature, humidity and weather prediction. The wind speed is obtained from self-designed anemometer system, the temperature is measured using LM35 sensor, and the humidity is assessed using DHT22. The wave height in the sea was predicted by calculating the wind speed value and effective average fetch value using neural network algorithm. The weather on the sea and on the beach were predicted by rain and light sensor. This weather prediction would be classified into three different results, namely raining, cloudy and bright. After some experiments, the result showed that the device can provide the information needed for fishermen and it has a high sensing accuracy. The humidity measurement had an average error of 1.1%, the temperature measurement had 1.42% average error, and 2.37% for the wind speed measurement. The wave height measurement system worked out and found the average wave height in Puger Beach 0.37 meters.